Pemberdayaan Perempuan dalam Upaya Pencegahan Kanker Serviks di Puskesmas Muara Bungo II - carmila, carmila; Handayani, Ayu Mustika (Universitas Baiturrahim, 2025)
Cervical cancer is a problem that mostly affects women due to infection with the Human papilloma virus. Cervical cancer is the type of cancer with the highest prevalence in women in Indonesia. The awareness of Indonesian women to carry out early detection of cervical cancer on a regular basis is still low. Due to the lack of public knowledge about cervical cancer including risk factors, prevention efforts and the public feel that Pap Smear and IVA tests are considered taboo. The purpose of this study was to determine the empowerment of women in cervical cancer prevention efforts at the Muaro Bungo II Health Center in 2022. This study was a cross sectional study. The population in this study were all women of childbearing age who were in the working area of ​​the Muaro Bungo II Health Center in 2021 as many as 4,127 people, the research sample was 97 people. The source of data in this study is primary data, data obtained through questionnaires used by Bivariate and Univariate analysts. The results showed that there was an influence of women's empowerment (counseling) on ​​knowledge with (p-value = 0.000 0.05), and attitude with (p-value = 0.000 0.05).